Organocatalytic Oxidation of Secondary Alcohols Using 1, 2‐Di(1‐naphthyl)‐1, 2‐ethanediamine (NEDA) (Eur. J. Org. Chem. 28/2014). Issue 28 (October 2014) - Al‐Hunaiti, Afnan; Räisänen, Minna; Pihko, Petri; Leskelä, Markku; Repo, Timo
Abstract : The cover picture shows the organocatalytic oxidation of alcohols with high selectivity towards secondary alcohols. The reaction is catalyzed by 1, 2‐di(1‐naphthyl)‐1, 2‐ethanediamine (NEDA) in the presence of tert ‐butyl hydroperoxide (TBHP) as a terminal oxidant. The secondary benzyl alcohols and even hindered cycloaliphatic secondary alcohols are oxidized in nearly quantitative yields. Enantiomers of NEDA were also studied in the oxidative kinetic resolution of racemic secondary alcohols, and good to excellent ee values were observed. Details are discussed in the Short Communication by T. Repo et al. on p.6141 ff .